A Competency-Based Education Case Study: A Mathematics Intervention for a Five-Year-Old with Autism Spectrum Disorder (ASD) - Tzohar-Rozen, Meirav; Kimhi, Yael; Cohen, Dalia (Journal of the American Academy of Special Education Professionals, 2022)
Early mathematics achievement is a significant predictor of future math learning. Current research shows that teachers lack knowledge in teaching methods for children with autism spectrum disorder (ASD). Specifically, research focusing on teaching mathematics in ASD is limited. A competency-based education (CBE) mathematics intervention was developed for a five-year-old boy with ASD in a naturalistic setting in his kindergarten and conducted as a single case study. The intervention was developed according to the specific needs of ASD, utilizing direct, embedded, and kinesthetic instruction. It incorporated support and ongoing assessment for teaching the standards-based mathematics curriculum. Two aspects were analyzed in the study: a) the kindergarten teacher’s process of intervention building and b) how this intervention advanced the student’s mathematical skills. The clinical and theoretical implications regarding the importance of an intensive, structured mathematical intervention for young children with ASD are discussed.